2019
DOI: 10.3126/jiom.v41i1.28591
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction and Insomnia among Elderly Community Dwellers of Lalitpur, Nepal

Abstract: Introduction: Life satisfaction during elderly is essential in ageing process. Globally, insomnia is a problem that degrades the health of elderly people, which also interferes with the quality of life. Methods: A descriptive cross-sectional study was conducted to identify life satisfaction and insomnia among 501 community dwellers elderly of Lalitpur by using structured interview schedule on socio-demographic information, Satisfaction with Life Scale (SWLS) to measure a life satisfaction and Pittsburgh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Globally, various studies were conducted on a global scenario which has shown variable findings about insomnia in older people (Brody, ; George, Paul, & Paul, ; Farazdaq, Andrades, & Nanji, ; Khagi, Timalsina, Chhantyal, Shiwakoti, & Maharjan, ; McCall, ). The prevalence of insomnia has been reported in the range of 12%–40% in the older population aged >65 years (Pathy, Sinclair, & Morley, ) whereas it has been reported to be 82.17% in India (Ahmad, Ansari, & Khan, ), 42.1% in Pakistan (Farazdaq et al, ) and 37.75% in China (Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, various studies were conducted on a global scenario which has shown variable findings about insomnia in older people (Brody, ; George, Paul, & Paul, ; Farazdaq, Andrades, & Nanji, ; Khagi, Timalsina, Chhantyal, Shiwakoti, & Maharjan, ; McCall, ). The prevalence of insomnia has been reported in the range of 12%–40% in the older population aged >65 years (Pathy, Sinclair, & Morley, ) whereas it has been reported to be 82.17% in India (Ahmad, Ansari, & Khan, ), 42.1% in Pakistan (Farazdaq et al, ) and 37.75% in China (Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%